THE USE OF FABLE STORY TROUGH STAD TECHNIQUE TO IMPROVE STUDENTS READING COMPREHENSION AT JUNIOR HIGH SCHOOL - Aisyah, Nur; AM, St. Asriati; Maharida (FKIP Unismuh Makassar, 2024)
This research aimed to find out to improve students’ reading comprehension that focused in determine the (main idea) and (conclusion) in the fable story in narrative text.This research employed pre-experimental research design with one group pre-test and post-test design. There were to variables: independent variable is the use of fable in terms of main idea and determining conclusion and dependent variable was the result of the test about improving students reading comprehension in terms of main idea and determining conclusion. The research findings showed that the students’ of SMP Pesantren Guppi Samata had low score in pre-test. After treatment, their post-test was significantly improved. The result of the research were the mean score of reading comprehension obtained by the students’ through pre-test was (main idea) 14.42 and (conclusion) 14.12 and post-test was (main idea) 22.95 and (conclusion) 21.48, with the t-test value is higher that t-table value (9,024 > 2,119). It meant that there was significant difference between before and after giving the treatment. It indicated that the alternative hypothesis (H1) was accepted and the null hypothesis (H0) was rejected. It was concluded that the using fable text was successful to increase the students’ capability in reading comprehension skills in reading English activity that improve them in narrative text.